THE INTRINSIC FATIGUE THRESHOLD OF 25CR2NI2MOV STEEL - SHEN XueCheng; DU YanNan; ZHU MingLiang; HUANG YuHui; XUAN FuZhen (Jixie qiangdu)
Fatigue crack growth tests of 25 Cr2 Ni2 MoV steel with two different heat treatments（550℃× 20 h,580℃× 20 h） were conducted at stress ratios R of 0.1,0.3,0.5 and 0.7,and the fatigue threshold,△Kth,and microscopic mechanism were investigated.Results showed that △Kth increased with the decrease of R,and the heat treatment had varied effects on △Kthunder lower R,while it had less effect under higher R.Fracture morphology observation showed that there existed a large number of facet morphology under lower R,while the facet morphology was gradually reduced with the increase of R.Additionally,the percentage of facet morphology followed a parabolic pattern with △K.It is indicated that R and heat treatment are important influencing factors on △Kth.The crack growth at higher R has weak effect of crack closure,representing the fatigue resistance of the material,and thus can be regarded as the intrinsic property of the material which can be estimated by the proposed model.